Estimation of the Status of Asiatic Lion (Panthera leo persica) Population in Gir Lion Landscape, Gujarat, India - Singh, A. P.; Nala, Ram Ratan (Indian Forester, 2018)
Carnivore conservation necessitates their population estimation. Owing to the elusiveness of carnivores that precludes direct observations, their population estimation is primarily a difficult task. The only population of Asiatic lion is found in the Gir forests and its adjoining landscape of Gujarat, India where under the strict and stringent protection of the erstwhile Nawab of Junagarh and subsequently the State-run Forest Department, their numbers have bounced back from the brink of extinction. At present 523 individuals live encompassing a total area of over 7000 km2 in the Gir and Greater Gir landscape in Gujarat, Western India. Asiatic lions are among the few large carnivores which have been managed and counted since a very long time. In this paper, elucidation of the history of population estimation of lions in the Gir forests, and put forth a new- management oriented yet scientifically robust technique of enumerating the status of Asiatic lions, an endangered carnivore nurtured and scientifically managed since 5 decades.